Effects of Breast Milk Fortification on Weight Gain in Low Birth Weight Infant Patients: Case Report - Ufiya Salma; Ferika Indarwati; Layli Anisah (Universitas STRADA Indonesia, 2024)
The WHO defines Low Birth Weight Infants (LBW) as babies born weighing less than 2500 grams regardless of gestational age. Low birth weight babies have a higher risk of developing complications and health problems. Therefore, interventions to improve babies' weight should be carried out. To assess the effect of providing breast milk fortification on babies' weight in neonatal patients with LBW. This study uses a case report by giving breast milk fortification to patients with LBW hospitalized in the PICU-NICU room at Temanggung Regency Hospital. The results of this case study showed that after being given breast milk fortification for six days.